Implikasi Batasan Makna Unsur "Persetubuhan" Dalam Pasal 411 Undang-Undang Nomor 1 Tahun 2023 Tentang Kitab Undang-Undang Hukum Pidana - Marcela Margaretha Hidianto; Evi Retno Wulan (Journal of Innovation Research and Knowledge, 2026)
Article 411 of the 2023 Indonesian Criminal Code (KUHP) expands the subjects covered by the offense of adultery but does not define the element of “sexual intercourse.” This normative gap has resulted in law enforcement authorities relying primarily on grammatical interpretation and classical legal doctrine, which traditionally limits sexual intercourse to penile-vaginal penetration. This normative-dogmatic study analyzes various forms of modern sexual activity to examine their conformity with the elements of the offense. The findings indicate that oral sex, anal sex, fingering, the use of sex toys, and same-sex sexual relations are categorically excluded from the scope of Article 411. This situation creates a legal safe haven, potentially allowing impunity for same-sex relations in private spaces, as well as a discriminatory anomaly that undermines the protection of the institution of marriage and citizens’ privacy rights. Therefore, establishing a uniform definition of “sexual intercourse” across all clusters of sexual offenses under the 2023 Indonesian Criminal Code is a strategic step toward closing legal loopholes, eliminating normative discrimination, and achieving legal certainty and substantive justice in the enforcement of Indonesian criminal law